Medical activities as an object of criminal law protection - M.V. Talan (Ученые записки Казанского университета: Серия Гуманитарные науки)
Taking into account the recent changes in the Criminal Code of the Russian Federation and the latest legal practice, the criminal law aspects of medical activity and crimes of medical workers against the individual, public health and public morality have been revealed. The criminal law assessment of adverse effects in medical activities, which can be assessed as accidents, medical errors, and professional crimes, has been given. The draft amendments to the Criminal Code of the Russian Federation on the encroachment on medical workers and obstructing the provision of medical care introduced by the Investigative Committee of the Russian Federation and the National Medical Chamber of the Russian Federation have been analyzed. The proposed changes in the design of the offense under Art. 124 of the Criminal Code of the Russian Federation “Failure to help the patient”, in particular about the criminalization of this act only when causing grievous bodily harm, have been considered. The proposals for further improvement of the criminal law in the part of the protection of medical activities with regard to the experience of European countries on crimes in the field of biomedical activity have been formulated.